Rancang Bangun E-Learning System Pada SMK Pratiwi Prabumulih Menggunakan PHP & MySQL - Juliansyah Juliansyah; Khana Wijaya; Muchlis Muchlis (Jurnal Pengembangan Sistem Informasi dan Informatika, 2021)
Along with the development of internet technology, e-learning began to be developed. Thus encouraging the authors to maintain the quality of education by applying e-learning at Pratiwi Prabumulih Vocational High School. E-learning is one of the tools to improve the efficiency and effectiveness of performance in the teaching and learning process. E-learning is a web-based system developed using the PHP programming language, HTML document types and MySQL to manage databases. The research method used is the system development method, namely the waterfall method. The system design method with a functional approach is described using UML (Unified Modeling Language). With the web-based e-learning system, the teaching and learning process can be accessed in all places anytime and anywhere without time restrictions. E-learning supports functions/features (upload and download) of data in the form of document content. E-learning is also able to display online questions or exams and score results so that it helps in the learning process